CONCURRENT MINISTERIAL POSITIONS: CONSTITUTIONAL AND AL-MAWARDI PERSPECTIVES - Ridho, Muhammad Ali (JOURNAL OF INDONESIAN COMPARATIVE OF SYARIAH LAW, 2023)
Concurrent positions is a political phenomenon that is very widespread nowadays in Indonesia, especially the concurrent ministerial positions from party cadres to even the general chairman of the party. This concurrent position results in the emergence of problems that are very vulnerable to abuse of power and conflicts of interest. The purpose of this study is to find out the arrangements for multiple ministerial posts based on article 23 of the law on state ministries, to find out Al-Mawardi's opinion on the issue of multiple positions, and to find out how the concept of an ideal ministerial position will be in the future. In this study the research method used by researchers is normative juridical, namely the statutory approach and the doctrinal approach. From a juridical perspective, the prohibition of concurrent ministerial positions has been regulated in Article 23 of law number 39 of 2008 concerning state ministries. But in that article the prohibition of holding multiple ministerial posts is not specifically regulated. Implicitly, Al-Mawardi explained that a minister must focus on devoting himself to the head of state in particular and the state in general. Because ministers must be the eyes and ears of the head of state, that is, they are required to be sensitive and observant about a problem that exists in that country. A minister must build integrity in the ministry to prevent the emergence of power instability. Therefore, an alternative concept for dealing with multiple ministerial positions can use a meritocracy system or zaken cabinet so that in the future ministers with ideal specifications will not result in conflicts of interest and abuse of power.Keywords: Concurrent positions, Minister, Constitutional, Al-Mawardi.